حقوق العمال في الرعاية االجتماعية واإلدارية في الفقه اإلسالمي - Abdulsoma, Thoarlim; Roslan, Ab Rahman; Anas, Yanya; Muhamad Zaharuddin, Zakaria (2017)
A worker's right to choose work, he has the right to social and psychological care,which tally with one’s interest and society’s.Also,the workers right to security and safety,because these embodents the element of freedom in human’s life and it is respected in Islam,the freedom to embrace Islam is a human right itself, the Muslims took the initiative to apply, pursuant to the teachings of their holy religion as a principle of human’s life, and social welfare rights ; the appropriate dressing at work, and the way to dress in Islam Lester body in order to protect someone from the view of people and defects, and apparelling differently from what has been underlined by Islam would cause overwhelming pride in people, and there exists some institutions which aims to maintain some of the freedom and indulgence, and organizational and management rights to form trade unions, which are regulatory and administrative rights for workers, and the unions are formed knowing the number of trade unions among themselves according to their will, whether on the level of trade or craft or geographic scope, and others, The research methodologies applied in the research were quantitative, in which it is field study that use qualitatively which is documentations research that apply deductive and inductive method. In executing this research, a combination of fieldwork and library research was conducted, The Result findings of the study are that women should choose the clothes that do not require great attention, which can be worn with clothes originally owned, and compensation for damages legitimate project, strike strike in Islamic jurisprudence, although it is permissible to say the most likely.